2000
DOI: 10.1021/np990328+
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and Mutagenic Evaluation of Two Annonaceous Acetogenins

Abstract: Annonaceous acetogenins represent a new class of bioactive compounds whose primary mode of action is the inhibition of NADH-ubiquinone oxidoreductase. Given the potential pesticidal use of such a class of compounds, we have further evaluated the antifeedant and insecticidal effects of squamocin and annonacin, two annonaceous acetogenins, on Spodoptera littoralis, Leptinotarsa decemlineata, and Myzus persicae. Additionally, to partially assess their environmental risk, we have also tested their mutagenicity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 33 publications
2
37
0
5
Order By: Relevance
“…Indeed, these compounds have been shown to inhibit complex I (NADH: ubiquinone oxidoreductase) in mitochondrial electron transport systems (Lewis et al, 1993); in addition, they are potent inhibitors of NADH oxidase of plasma membranes (Morré et al, 1995); these enzymes are all found in P. falciparum and the effects of inhibitors impair parasite oxidative and cytosolic ATP production, leading to apoptosis. Acetogenins have been also reported as potent cytotoxics with insecticidal, ascaricidal, fungicidal, antiparasitic, bactericidal and antiplasmodial activities (Rakotomanga et al, 2004;Guadaño et al, 2000). Beside the few previous works reported above, Boyom (2004) also showed that essential oils from the stem bark of P. suaveolens and U. angolensis have in vitro inhibitory potential against P. falciparum W2.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, these compounds have been shown to inhibit complex I (NADH: ubiquinone oxidoreductase) in mitochondrial electron transport systems (Lewis et al, 1993); in addition, they are potent inhibitors of NADH oxidase of plasma membranes (Morré et al, 1995); these enzymes are all found in P. falciparum and the effects of inhibitors impair parasite oxidative and cytosolic ATP production, leading to apoptosis. Acetogenins have been also reported as potent cytotoxics with insecticidal, ascaricidal, fungicidal, antiparasitic, bactericidal and antiplasmodial activities (Rakotomanga et al, 2004;Guadaño et al, 2000). Beside the few previous works reported above, Boyom (2004) also showed that essential oils from the stem bark of P. suaveolens and U. angolensis have in vitro inhibitory potential against P. falciparum W2.…”
Section: Discussionmentioning
confidence: 95%
“…Methoxy methylated derivatives, squamocin (MOM) (14) and motrilin (MOM) (15) were obtained by adding N,N-diisopropylethylamine and methoxymethyl chloride to a dichloromethanic solution of natural ACG under a nitrogen atmosphere. (3 g), boiled and milled bean (250 g), wheat germ (12.5 g), ascorbic acid (1.5 g), agar agar (12.5 g), methyl p-hydroxybenzoate (1.5 g), formaldehyde (4 mL of a 38 % water solution), and water (500 mL).…”
Section: Structural Modification Of Acgmentioning
confidence: 99%
“…ACG acetylated (OAc) derivatives: squamocin (3 OAc) (11), molvizarin (3 OAc) (12) and motrilin (3 OAc) (13), and their methoxy methylated (MOM) derivatives: squamocin (MOM) (14) and motrilin (MOM) (15) (Figure 2) were synthesized and purified, and then characterized by spectroscopic techniques (Table 1 and Table 2). …”
Section: Annonaceous Acetogeninsmentioning
confidence: 99%
See 2 more Smart Citations